Cerita Rakyat sebagai Kristalisasi dan Media Internalisasi Nilai Pendidikan Karakter pada Masyarakat Kotawaringin Timur: Folklore as Crystallization and Media for Internalization of Character Education Values in Kotawaringin Timur Society - Putri, Tika Pebryani Ratna; Anggraini, Gita; Nengsih, Putri Rahayu (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Folklore is part of the culture of the community that speaks it, a concrete form of creativity, feeling, and will that becomes the crystallization of values and a reflection of the character of the people. It contains hopes and references for the nobility of character and the outlook on life of the community that speaks it, so that it becomes a transfer of values from the previous generation to the next generation, where there is character education that can be conveyed. This study aims to find and present a general description or information about the folklore of East Kotawaringin. The research method uses a qualitative approach with the ethnopedagogy method. The research locus is Baamang District, East Kotawaringin Regency. Data were collected using interviews, observations, and literature studies. Analysis was carried out through the stages of data reduction, data presentation (display), conclusion, and verification. The results found were information and facts about folklore as a crystallization of values and a reflection of the character of the community. There are values in the folklore of East Kotawaringin, including norms towards oneself, others, the environment, and God. The existence of these values makes folklore can be used as a medium for character education.